Controversies in the Management of Endometrial Carcinoma - Ying Zhang; Jian Wang (Obstetrics and Gynecology International)
Endometrial carcinoma is the most common type of female genital tract malignancy. Although endometrial carcinoma is a low grade curable malignancy, the condition of the disease can range from excellent prognosis with high curability to aggressive disease with poor outcome. During the last 10 years many researches have provided some new valuable data of optimal treatments for endometrial carcinoma. Progression in diagnostic imaging, radiation delivery systems, and systemic therapies potentially can improve outcomes while minimizing morbidity. Firstly, total hysterectomy and bilateral salphingo-oophorectomy is the primary operative procedure. Pelvic lymhadenectomy is performed in most centers on therapeutic and prognostic grounds and to individualize adjuvant treatment. Women with endometrial carcinoma can be readily segregated intraoperatively into “low-risk” and “high-risk” groups to better identify those women who will most likely benefit from thorough lymphadenectomy. Secondly, adjuvant therapies have been proposed for women with endometrial carcinoma postoperatively. Postoperative irradiation is used to reduce pelvic and vaginal recurrences in high risk cases. Chemotherapy is emerging as an important treatment modality in advanced endometrial carcinoma. Meanwhile the availability of new hormonal and biological agents presents new opportunities for therapy.